Oil refineries in the 21st century : energy efficient, cost effective, environmentally benign - Ocic, Ozren (Wiley-VCH, 2005)
"Here, the author provides a detailed and well-founded approach to the methodology, information and criteria necessary for analyzing energy use, economics and the environmental impact, as well as practical solutions for fulfilling the requirements of the Kyoto agreement. In addition, he describes in sufficient detail the energy streams within a refinery." "A practical guide for refinery engineers, managers, and consultants, as well as all engineers involved in the design of process technologies, in developed as well as developing countries."--BOOK JACKET.